Modelling the Embedded Control System Using iUML-B Pattern State Machine - Han Peng; Chenglie Du; Lei Rao; Zhouzhou Liu (Journal of Control Science and Engineering)
Developing the formal model based on the Event-B design pattern is an excellent method to improve the development efficiency of the embedded control system and improve the reusability of the formal model. However, the instantiation of the Event-B design pattern requires the manual writing of a large number of model codes, which brings a great deal of learning cost and coding burden to the engineering staff. In this paper, we propose a modelling approach for formal development of control systems based on the application of iUML-B state machine patterns to model the four synchronization patterns of the typical control system. Then, we use the instantiation of iUML-B pattern state machine to establish a typical multilevel control system's Event-B model. The simulation results show that the event trace of the model obtained using our method is the same as that of the corresponding model obtained using the traditional Event-B design pattern. Compared with the traditional Event-B design pattern method, our method can greatly reduce the manual coding burden in the modelling process. The system model expressed using the iUML-B pattern state machine can be easily mapped to the labelled transition system so as to verify the behavioural properties of the model.